PEMBUATAN ARANG BIOBRIKET DARI LIMBAH KUIT KOPI DI PEKON GUNUNG SARI KECAMATAN ULUBELU KABUPATEN TANGGAMUS - Hardoyo, Hardoyo; M W Wardana; Alif Maulana Al Hussain; Rahmad Rizki Jayadi; Fitri Rhoisatun; Achmad Irwansyah; Guntur Prasetyo; Teuku Arie Mauliza Sunata; Bayu Afrinaldo Arief; Muhammad Azinuddin (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The Community Service (PKM) activity entitled "Making Biobriquette Charcoal from Coffee Husk Waste in Pekon Gunung Sari, Ulubelu District, Tanggamus Regency" aims to provide knowledge and skills to the community in processing coffee husk waste into environmentally friendly alternative fuels. Previously unused coffee husk waste is converted into biobriquette charcoal through a simple process, namely burning, grinding, mixing with adhesive, molding, and drying. This activity was carried out through socialization, direct training, and discussions with the community. The results of the activity showed that the community was very enthusiastic and interested in developing biobriquette production because it was considered economically and environmentally beneficial. In conclusion, the utilization of coffee husk waste into biobriquette charcoal can help reduce environmental pollution and become a new business opportunity for the community in Pekon Gunung Sari.